Update on primary headache associated with sexual activity and primary thunderclap headache. (March 2023) - Lin, Po-Tso; Chen, Shih-Pin; Wang, Shuu-Jiun
Background: This narrative review aims to provide an update on primary headache associated with sexual activity and primary thunderclap headache. Methods: We conducted a literature search on PubMed with the keywords "headache associated with sexual activity", "sexual headache", "orgasmic cephalalgia", and "coital cephalalgia" in addition to "thunderclap headache" to assess the appropriateness of all published articles in this review. Results: Primary headache associated with sexual activity is a "primary" headache precipitated by sexual activity, which occurs as sexual excitement increases (progressive at onset), or manifests as an abrupt and intense headache upon orgasm (thunderclap at onset) or combines these above two features. Primary headache associated with sexual activity is diagnosed after a thorough investigation, including appropriate neuroimaging studies, to exclude life-threatening secondary causes such as subarachnoid hemorrhage. According to the criteria of the third edition of the International Classification of Headache Disorders, primary thunderclap headache is also a diagnosis by exclusion. The pathophysiology of primary headache associated with sexual activity and primary thunderclap headache remains incompletely understood. Treatment may not be necessary for all patients since some patients with primary headache associated with sexual activity and primary thunderclap headache have a self-limiting course. Conclusion: A comprehensive neuroimaging study is needed for distinguishing primary headache associated with sexual activity or primary thunderclap headache from secondary causes. Primary headache associated with sexual activity and primary thunderclap headache are self-limited diseases and the prognoses are good, but some patients with primary headache associated with sexual activity may have a prolonged course.